Development of a methodology for measuring the parameters of class A fire extinguishing by a powder fire extinguishing modular installation of short-term action in the scheme of extinguishing locally on the surface - Kitsak, Анатолий Ильич; Palubets, Сергей Михайлович; Nadtochii, Денис Николаевич; Lobach, Денис Сергеевич (Journal of Civil Protection, 2022)
Purpose. Development of a methodology for measuring the parameters of extinguishing class A fire with a modular powder extinguishing system (MPES) of short-term action in the extinguishing scheme locally on the surface and experimental determination of the values of these parameters that ensure effective extinguishing of a fire of this class. Methods. The achievement of purpose was carried out by the development of procedures for measuring the parameters of class A fire extinguishing (fire extinguishing time, intensity of the supply of extinguishing powder to the combustion zone, speed of powder particles in this zone, and specific consumption of powder for extinguishing the fire) and experimental determination of the values of these parameters in conditions close to the natural when using the MPES. Findings. The conditions for effective extinguishing of class A fire with a general-purpose extinguishing powder with short-term effect on the fire source in the extinguishing scheme locally on the surface are determined.A method of measuring the parameters of extinguishing fires of class A with the MPES of short-term action in the extinguishing scheme locally on the surface has been developed.Experimental studies of the effectiveness of extinguishing class A fire with a general-purpose extinguishing powder with a short-term effect on the fire source (duration ~ 1 s) and various extinguishing modes have been carried out.Experimental dependences of the average extinguishing time and the average specific consumption of the extinguishing powder of the «Vekson-ABC 25» type for extinguishing a model fire of subclass A1 on the average intensity of the powder supply to the combustion zone in the extinguishing scheme locally on the surface are constructed.It has been established that there is an optimal value of the intensity of the supply of extinguishing powder to the fire source, at which the extinguishing time and, accordingly, the specific consumption of powder for extinguishing the fire are minimal. This value is recommended as a normative one when evaluating the fire extinguishing capacity of the MPES used to extinguish fires of subclass A1 with the fire extinguishing powder «Vekson-ABC 25». Application field of research. Solving the problems of increasing the reliability of extinguishing fires of class A by MPES and improving the methodology for assessing their extinguishing ability.